KONFLIK BATIN TOKOH MUSTAFA DALAM NOVEL TEMPAT PALING SUNYI KARYA ARAFAT NUR - Razzaq, Agung Abdul; Sutejo, Sutejo; Setiawan, Heru (Jurnal Bahasa dan Sastra, 2022)
Literature is the art of human thought. Literary works are mostly written in beautiful language and providing general insight into human problems and their conflicts. Conflict is essentially a problem that occurs in society. Conflict occurs because of a need and desire that is not achieved, then an unpleasant feeling arises inside. This study aims to describe the inner conflict of Mustafa’s character in Arafat Nur’s novel Tempat Paling Sunyi. The inner conflict in Mustafa’s character is analyzed using Adler’s theory of Individuality Psychology. Adler’s theory is a psychological theory of personality which in his view problems are always social, so that personality is defined as a character or character that stands out in humans. Therefore, the research approach used is a qualitative descriptive method. The data in this study are excerpts in the from of word and sentences in Arafat Nur’s novel Tempat Paling Sunyi. From the result of the study it can be concluded that in Arafat Nur’s novel Tempat Paling Sunyi, there are six inner conflicts according to Alfred Adler’s view, as follows: struggle to be superior, subjective perception, unity of personality, social interest, creativity, and life style.